Comparative Study of Palm Oil Fuel Ash (POFA) and Rice Husk Ash (RHA) as Supplementary Cementitious Material (SCM) in Brick: A Review: ENGLISH - ZAMRI, NURUL SYADZA BINTI (Progress in Engineering Application and Technology, 2021)
This study is to review the properties of brick containing Palm Oil Fuel Ash (POFA) and rice husk ash (RHA) as supplementary cementitious material (SCM) in brick. The use of POFA can reduce carbon dioxide (CO₂) emissions from cement brick and RHA as a new replacement for natural material, sand, clay, and cement. The study includes characterization, optimum percentage of POFA and RHA incorporated with water absorption and compressive strength. When incorporated at various levels of POFA and RHA quantities as the partial cement substitution into the brick, the findings will be demonstrating the compression strength, density and, water absorption of brick. Based on the previous study, brick density and compressive strength decreased as the replacement percentage increased and this can be a method for a lightweight brick and as a sustainable brick. RHA is good in water absorption despite greater porosity and high pozzolanic. The result shows that POFA and RHA can benefit the lightweight brick as a medium for waste management for cement and sand replacement.